ONLINE DISPUTE RESOLUTION (ODR) AS AN ALTERNATIVE FOR ELECTRONIC TRANSACTION DISPUTE SETTLEMENT - Soesi Idayanti; Toni Haryadi; Evi Indriasari (Universitas Slamet Riyadi, 2021)
The development of communication and information technology has an impact on all aspects of human life. Technology has changed the business world from traditional trading patterns to a more modern trading system, namely an online trading system known as electronic commerce (e-commerce). Electronic commerce/electronic-commerce/e-commerce is the distribution, sale, purchase, marketing of goods and services that rely on electronic systems, such as the internet, television, or other computer networks. The agreement is also made online, basically, an online sale and purchase agreement (e-commerce) is the same as a general sale and purchase agreement, which requires an agreement between the seller and the buyer regarding the goods or services being traded and the price for the goods or services. Alternative Dispute Resolution (ADR) is dispute resolution out of court. that the parties to the dispute by mutual agreement are free to choose the forms and procedures contained in the alternative dispute resolution and will be applied in dispute resolution. Agreements made online are expected to be completed online as well. For this reason, alternative dispute resolution is sought which is expected to facilitate the dispute resolution process with online transactions. One of the breakthroughs is by using an online arbitration model known as Online Dispute Resolution (ODR) so that the disputing parties can settle wherever they are.The method used is through normative legal research, which is a scientific research procedure to find the truth based on scientific logic from the normative side, carried out to produce arguments, theories, or new concepts as prescriptions in solving problems at hand. The nature of this research is descriptive-analytical. In the future, this discussion will open a new way to facilitate the Indonesian people, especially those seeking legal certainty, in resolving disputes using ODR